The Impact of Nutritional Counseling to Nutritional Knowledge and Energy Intake among Obese Children in Junior High School - Lastri Asmuniati; Dewi Marhaeni Diah Herawati; Julistio TB Djais (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Obesity has a serious impact on health, leading to not only premature mortality but also to long-term morbidity. Factors that contribute to obesity are genetic and lifestyle. This study aimed to analyze the impact of nutritional counseling on nutritional knowledge and energy intake among obese children in junior high school.Methods: This quasi-experimental study was conducted in Jatinangor in September–November 2014 using a consecutive sampling until 25 students had reached. The inclusion criteria were junior high school students with BMI z-score per age >2 obese categories. Nutritional knowledge and energy intake were measured using a 24-hour recall test, conducted before and after 2 weeks of nutritional counseling. Data were analyzed using a paired t-test.Results: The average of nutritional knowledge before counseling was 46.72±2.63 and after counseling was 65.92±2.92 (p<0.001), whereas the average in energy intake before counseling was 1769.68±113.32 and after counseling was 1397.52±114.31 (p=0.006).Conclusions: There is an increase knowledge and decrease energy intake among obese children in junior high school students in Jatinangor subdistrict after nutritional counseling. A better understanding among obese children needs to be highlighted and nutrition education and counseling should be given in schools.